Yielding to marketocracy? Assessing the Ruggie Framework on business and human rights - Onyango, J Oloka (University of Pretoria, 2010)
A dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Prof J Oloka Onyango, Faculty of Law, Makerere University. Uganda.